Kpopification: Politicizing Fandom in Indonesia's 2024 Presidential Election Campaign of Anies Baswedan - Yasinta, Jasmine Rizky El; Nanda, Elvira Chandra Dewi Ari; Aurora, Kezia; Wibowo, Isac Cristopher; Alhuda, Muhammad Ahsan; Purwaningtyas, Mashita Phitaloka Fandia (UIN Sunan Gunung Djati, 2025)
In the 2024 presidential election, a fan community (fandom) named Humanies emerged to support one of the presidential candidates, Anies Baswedan. This support began with the emergence of @aniesbubble and @olpproject accounts on social media X, which carried out many activities that adopted fandom culture, such as crowdfunding and fan-projects to support their idol. This research aims to find out how fandom culture is utilized in Anies Baswedan’s political campaign on social media X, how the utilization of fandom politicization affects the gen-Z view about Anies Baswedan in the 2024 Presidential Election, and to determine the effectiveness of the campaign. The research method is a mixed-method that combines qualitative and quantitative approaches, conducted with netnography and survey. The result of this research shows that @aniesbubble and @olpproject accounts successfully adopted fandom culture as a campaign tool for Anies Baswedan. In addition, this research finds out that the politicization of fandom proved to have an influence of 79% on gen-Z’s views on Anies Baswedan and the campaign proved to be effective.